Strengths-based Nursing and Healthcare in maternities: rethinking practices and continuity of care* - Silva, Otília Beatriz Maciel da; Bernardino, Elizabeth; Encarnação, Paula (Revista da Escola de Enfermagem da USP, 2022)
Objective: To identify elements of the Strengths-Based Nursing and Healthcare in the maternity nurses care practice in a perspective of continuity of care. Method: Qualitative exploratory-descriptive study. A focus group was used for data collection, seven meetings were held with 18 nurses between August 2019 and January 2020, starting from a priori categories: “problem-based nursing care” and “strengths-based nursing and healthcare”. Results: In the first category, nurses’ care is centered on problems identified in women; they keep a hierarchical relationship and a prescriptive posture based on a biomedical model. In the second category, care is focused on singularity, empowerment, self-determination, learning, collaborative partnership, and promotion of women’s health, based on a holistic nursing model. Conclusion: Although nurses use the biomedical model in their care practice, many of them already use the framework elements empirically. Applying this theoretical framework allows nurses to shift the focus of their attention from the disease to the person/family, promoting health and the continuity of care in a holistic way.